Gambaran Sleep Hygiene pada Remaja - Rositianti, Rositianti; Lukman, Mamat; Yulianita, Henny (Journal of Telenursing (JOTING), 2024)
This study aims to describe sleep hygiene in junior high school adolescents. The method used is descriptive quantitative with a cross-sectional approach. The results of the study showed that 76.2% of teenagers at SMP Negeri 2 Pamulihan, Sumedang Regency had moderate sleep hygiene, 20% had good sleep hygiene, and 3.8% had poor sleep hygiene. In conclusion, almost all adolescents have poor sleep hygiene. Keywords: Adolescents, Sleep Hygiene, Sleep